The oligarchic-rationalist foreign policy model of South Africa's De Klerk government, 1989-1994 - Landsberg, Chris (Faculty of Humanities, University of the Free State, 2013)
It is almost 20 years since South Africa became a constitutional democracy, and it is a good time to reflect not only on the past two decades but on the transition period of 1989-1994. When Frederik Willem de Klerk became the National Party “hoofleier” or chief leader, and eventually executive President of South Africa on 20 September 1989, one could not have imagined the impact he and his party would have, not only on the country’s domestic and international politics, but also on the decision-making processes and structures of the Republic. In this article the focus falls on foreign policy making and formulation under the De Klerk government during the period 1989 to 1994, as well as dissecting the agencies that were entrusted with operationalising foreign policy. Emphasis is on De Klerk’s oligarchic-rationalist foreign policy model which stressed civilianisation and the restoration of the cabinet in decision making, and a move away from PW Botha’s militaristic and securocratic methods of decision making. Indeed, when De Klerk addressed parliament in his epoch-making speech on 2 February 1990, and embarked on his de-isolation strategies for the pariah state, he appreciated the need for the democratisation of decision and policy formulation structures that would help to end decades of ostracism and global banishment.
Keywords: De Klerk’s oligarchich-rationalist foreign policy; Foreign policy executive; Innercircle; Rational actor model; Reformist actions; Lack of international experience; A quick learner; Internationalisation and de-isolation; Normalisation; Reform; Open door approach; Civilianisation; Constitutional negotiations; Transitional Executive Council; “New” diplomacy